Analisis perbandingan metode tafsir al-Muqaran dan al-Mawdhu’i dalam kajian tematik al-Qur’an - Saputra, Mhd. Aidil; Alwizar, Alwizar (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This article explores two prominent approaches in Qur’anic exegesis: al-Muqaran (comparative) and al-Mawdhu’i (thematic) methods. Employing a qualitative library-based methodology, the study investigates the theoretical foundations, procedural steps, and practical applications of both methods. The al-Muqaran method focuses on comparing interpretations from various exegetes or between related verses to identify similarities and differences in hermeneutical perspectives. In contrast, the al-Mawdhu’i method collects all Qur’anic verses related to a specific theme and analyzes them holistically to construct an integrated understanding of the subject. This article presents examples of both methods and evaluates their respective strengths and limitations. The findings reveal that while the comparative method enriches inter-textual and cross-exegetical dialogue, the thematic method offers systematic insights on contemporary issues. The study concludes that both approaches are complementary and vital in responding to the epistemological and practical demands of modern Qur’anic studies.